Structural analysis of rhodopsin states in megabody complexes - David Salom; Diana S. Suder; Wei Huang; Arum Wu; Els Pardon; Jan Steyaert; Philip D. Kiser; Derek J. Taylor; Shane Gonen; Krzysztof Palczewski (Proceedings of the National Academy of Sciences, 2026)
Rhodopsin, the most intensively studied G protein–coupled receptor (GPCR), is activated by light-induced isomerization of its chromophore 11- cis -retinal. This study employed cryogenic electron microscopy (cryo-EM) to investigate rhodopsin structure using a megabody (Mb7) as a negative allosteric modulator. Three distinct cryo-EM structures were solved: ground-state rhodopsin, photoactivated rhodopsin, and apo-rhodopsin, all in complex with Mb7. Photoactivated rhodopsin and apo-rhodopsin, both in complex with Mb7, maintain a conformation remarkably similar to ground-state rhodopsin rather than adopting a Meta-II-like conformation. Structural elements, including the conserved residues of the NPxxY motif and the ionic lock, remain in positions corresponding to inactive rhodopsin. The megabody forms extensive interactions with rhodopsin’s extracellular loop 2, N terminus, and glycans. The findings demonstrate that Mb7 stabilizes photoactivated rhodopsin in a Meta-I-like conformation, preventing progression to the active Meta-II state through specific immobilization of the extracellular domain. This work establishes a foundation for cryo-EM-guided discovery of ligands modulating rhodopsin.